Rare Case of Dental Implantation in the Segment with Residual Filling Material in the Mandibular Canal - Yury Georgievich Sedov; Kamil Nail’evich Khabiev; Zulfiya Iltuzurovna Yarulina; Vasiliy Stanislavovich Tarasuk; Anatoliy Mikhailovich Avanesov; Nikolay Ivanovich Sergeev; Vitaliy Georgievich Pantsulaya; Irina Gennad’evna Sedova (Case Reports in Dentistry)
Dental implantation is the most popular method of restoring lost teeth. There are risk factors for dental implantation. These risk factors include the localization of residual filling material in the lumen of the mandibular canal in the selected jaw segment for implantation. A rare clinical case of dental implant placement with preservation of the safety zone relative to the residual siler in the mandibular canal is presented. A surgical guide was used for precise positioning. The treatment protocol was carried out without an immediate loading stage to monitor the possible development of symptoms.